Spoken language bilingualism for deaf students: Parental decision-making - Simpson, Melanie (Working papers in Applied Linguistics and Linguistics at York, 2023)
Language has always been at the core of our practice in deaf education, but in the current context, it is time to explore new language possibilities for deaf students. Over the past two decades, the combination of widespread implementation of universal newborn hearing screening (UNHS) and early amplification with hearing technologies, including cochlear implants (CIs), has afforded meaningful access to spoken language during the critical language development period for most deaf children. Early interventionists and educators have taken a new perspective of encouraging spoken language bilingualism in home languages and the majority language. This shift has opened doors to education in spoken language bilingual settings (e.g., French immersion), doors formerly closed to deaf students. This paper presents some preliminary qualitative data, highlighting parent decision-making, from a mixed method case study of deaf Francophone participants (N = 4) enrolled in grades 4-12 at French minority schools in southern Ontario.